Causes of Cerebral Palsy in Sulaimani - Omar Ala Ahmed; Aso Faeq Salih (Advanced Medical Journal)
Background and objectives:Cerebral palsy is a common neurodevelopmental condition encountered by pediatricians The condition may present itself in many different clinical spectra. The etiological and risk factors are many and an awareness of the interplay of multiple factors in the causation of cerebral palsy is crucial. The aim of the study is to evaluate the risk factors of cerebral palsy in Sulaimani city. A better understanding of the etiology of cerebral palsy is necessary for preventive strategies and treatments to be developed.